Kampanye Pelecehan Seksual oleh Komunitas Sosial Online @Perempuan Berkisah melalui Instagram - Audia Syifa Octaviani; Irhamni Rahman (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Women's stories on Instagram as an online community that is currently embraced 107 thousand individual followers by intensively doing online social campaign and discuss case by case of women who experiencing sexual harassment through content on the account. So, based on Field findings following forms of social campaigns, namely personal stories, infographics and illustrations, inspirational quotes, calls to action, legal and rights education, and Testimonials experienced by the social community of @perempuanberkisah accounts. This study uses a descriptive qualitative research method. Collection The data was carried out by interviews, observations, and documentation. Results It also shows that the women who are victims are expressing their feelings and insecurities. Victims They tend to have that the outside world is a threat to them. So that there is a need for increased awareness, change in attitude and behavior change. Victims experienced by adolescents to adults and preventive measures to prevent harassment and violence sexual recurring in the victim. Hope by sharing this story, can provide moral support for other women who may feel hesitate or embarrassed to speak up. Women who dare to share stories are inspiration big and this further motivates to continue fighting for the rights of fellow women.